MOLECULAR DIAGNOSIS AND CHEMOTHERAPY OF TRYPANOSOMA EVANSI IN NILI-RAVI BUFFALOES AT DISTRICT OKARA (PAKISTAN) - W. Shahzad; R. Munir; M. S. Khan; M. U. D. Ahmad; M. Iqbal (Journal of Animal and Plant Sciences, 2012)
A total of 144 blood samples were collected from apparently emaciated and anemic Nili-Ravi buffaloes in and around Livestock Experiment Station Bahadurnagar Okara during December, 2008 to May, 2009 including all age groups and either sex. They were screened for the presence of trypanosomes through stained (Hemacolor™, Merck) thin blood smears. The cases were confirmed as T. evansi through polymerase chain reaction (PCR). DNA of the trypanosomes was isolated using trizol reagent. The assay employed primers ESAG 6/7 specific for 237 bp fragment from T. evansi genomic DNA which was subsequently electrophorised and analyzed on UV transilluminator. Eight samples (5.5%) were positive microscopically while 16 samples (11.11 %) were found positive through PCR, indicating the specificity and sensitivity of PCR for surveying the disease in epidemiological studies. All the diseased buffaloes were treated with diminazene aceturate (FA.TRY.BANIL R.T.U., FATRO, Italy @ 3.5 mg/ kg body weight). The treated animals were found negative for the parasite both microscopically as well as through PCR, 48 hours post injection indicating the sensitivity of this drug to T. evansi in buffaloes.
Keywords: T. evansi; Nili Ravi buffalo; PCR; Diminazene aceturate